Strategi Bisnis Pada Klinik Kesehatan Menggunakan Analisis SWOT - Fareiz Aulia Firman; Deti Mulyanti (Pusat Riset dan Inovasi Nasional, 2023)
This study intends to determine the challenges to health clinics in Indonesia and how SWOT analysis is utilized as a strategy to boost competitiveness. Descriptive qualitative methodology is the research technique used. There are three types of SWOT analysis that are used: descriptive analysis, SWOT matrix, and SWOT diagram analysis. The method of data collecting used in this study is literature. According to the study's findings, SWOT analysis as a method to boost competitiveness needs to be reevaluated in order to advance these clinics across Indonesia with good performance from both within and outside the service business unit and health products.